“Medieval” and “Modern” Conceptions of the Colours of Light in Early Modern England and Isaac Oliver’s Portrait Miniatures - Raphaëlle COSTA DE BEAUREGARD (E-REA)
The usual distinction between ornamental and naturalistic styles is traditional when Nicholas Hilliard’s works and treatise The Art of Limning (c. 1600) are compared to Isaac Oliver’s, his pupil. However, the cultural context of the miniature court portrait in early modern England also shows two other traditions, i.e. the strategies to capture light in colours in two schools, one defining light as rays, another defining light as the limit between two colours. In either theory, the core of the subject is our perception of colours as/of/in light. This article will consider several early modern miniatures, but particular attention will be paid to two portrait miniatures by Isaac Oliver when he was at the height of his reputation not only as Hilliard’s pupil but also as an independent artist: John Donne (1616) and the Head of Christ (c. 1610).